Metrics for minimising environmental impacts while maximising circularity in biobased products: The case of lignin-based asphalt. (15th December 2022) - Corona, B.; Hoefnagels, R.; Vural Gürsel, I.; Moretti, C.; van Veen, M.; Junginger, M.
Abstract: Achieving a circular economy (CE) is seen by society and policymakers as crucial to achieving a sustainable, resource-efficient, renewable and competitive economy. Given the current threat of climate change, we must develop new products that not only maximise the circularity of resources but also minimise climate change impacts. While these two goals are usually aligned, trade-offs exist. For instance, recycling biobased asphalt is a better end-of-life option than landfilling from a resource efficiency perspective. However, landfilling of biogenic non-biodegradable material leads to permanent carbon storage and, therefore, climate benefits. To fully understand the potential benefits and impacts of biobased circular innovations, we need metrics to capture their complexity from both a circular and climate point of view. This study explores the use of different circularity and sustainability metrics to understand the impacts and trade-offs of lignin-based versus bitumen-based asphalts. The analysis is done by calculating the Material Circularity Index (MCI) and two newly developed indicators quantifying the biogenic carbon storage (BCS) of products (BCS100 and c-BCS) while following the CE principles. In addition, the impacts regarding climate change, life cycle costs and ECI (environmental costs indicator) are also provided. Based on the MCI, it can be concluded that lignin-based asphalt roads have slightly higher material circularity than their bitumen-based counterparts. The BCS analysis indicated that the least circular lignin-based alternative sequesters the highest amount of carbon in the long term due to permanent storage in foundations. Despite these trade-offs, the results from the newly developed BCS indicators allowed to align both climate and circularity goals, guiding policymakers and industry actors to implement circular biobased strategies where the value of biobased materials is optimised. Finally, this article discusses the use of different circularity and environmental metrics for decision making in the context of a circular biobased economy. Highlights: Two new metrics measuring biogenic carbon storage were developed. Material circularity and climate change goals are not necessarily aligned. Lignin-based asphalt has slightly higher circularity than bitumen alternatives. Circularity and life cycle indicators should be combined to understand trade-offs.